2011
DOI: 10.5812/kowsar.1735143x.749
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and Hepatitis B Virus Infection: Epidemiology and Risk Factors in a Large Cohort of Pregnant Women in Lorestan, West of Iran

Abstract: BackgroundThere are little data on the prevalence of serological markers of hepatitis B and hepatitis C viruses in pregnant women in Iran.ObjectivesThis study was designed to determine the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection among pregnant women in Lorestan, west of Iran.Patients and MethodsSerum samples of 827 pregnant women who lived in rural (36.8%) and urban areas (63.2%) of Lorestan were collected during 2007-2008. Data were obtained through questionnaires. Samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
1
16
4
2
Order By: Relevance
“…Even though the difference was not statistically significant, the prevalence of HBsAg was higher in the age group between 21 and 30 years old, 7 (3.2%), which is in line with Debre-Tabor town of Ethiopia 37 where higher HBsAg prevalence was reported among the age group <30 years old. However, it disagrees with the results reported in Iran 27 and Jimma, 32 Ethiopia where pregnant women with the age group between 30-34 years and greater than 40 years old had higher prevalence of HBV infection. The high prevalence among this age group was consistently reported in several other studies.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Even though the difference was not statistically significant, the prevalence of HBsAg was higher in the age group between 21 and 30 years old, 7 (3.2%), which is in line with Debre-Tabor town of Ethiopia 37 where higher HBsAg prevalence was reported among the age group <30 years old. However, it disagrees with the results reported in Iran 27 and Jimma, 32 Ethiopia where pregnant women with the age group between 30-34 years and greater than 40 years old had higher prevalence of HBV infection. The high prevalence among this age group was consistently reported in several other studies.…”
Section: Discussioncontrasting
confidence: 95%
“…The HCV's finding of our study (1.8%) is inconsistent with previous reports among pregnant women in Sudan (0.6%), 43 Benin City, Nigeria (0.8%) 44 and Iran (0.2%). 27 However, it is in line with Egypt (1.75%), 45 Gondar, Ethiopia (1.3%). 39 In contrast, higher prevalence of HCV was reported from Yemen (8.5%).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The prevalence of HBsAg in our study is alike in the studies reported in Libya 1.5%, in Algeria 1.6% [17], in Mexico 1.65% [18], in Amritsar (India) 1.19% [19], in Isfahan (Iran) (1.56%) [20] and in Bulgaria 2.26% [21]. However, the prevalence of HBsAg in the present study is higher than the studies reported in Lorestan West of Iran (0.7%) [22], in India (0.9%) [23], in Punjab (Northern India) (1.1%) [24], and in Peshawar, Pakistan (1.16%) [25]. On the other hand, higher prevalance rates were reported in Bahir Dar (Northwest of Ethiopia) (3.8%) [26], in Mayotte Indian Ocean (France) (3.4%) [27], in Southwestern Nigeria (7.1%) [28], in Cameroon (9.7%) [29], in Eastern Ethiopia (6.9%) [30], in Southern Ethiopia (7.8%) [31], in Bahir Dar (Northwest Ethiopia) once again (4.4%) [32], and in Sana'a Yemen (10.8%) [33].…”
Section: Discussionsupporting
confidence: 64%
“…Researches have shown that the introduction of HBV vaccination has resulted in lower intrafamilial transmission of HBV (19). Researchers have suggested screening pregnant women for HBV infection to reduce perinatal transmission (20). The transmission may be present even after vaccination, especially in neonates of mothers with positive results for HBeAg.…”
Section: Discussionmentioning
confidence: 99%